The Prophetic Speech to Women - Agha, Asma Alzroog; Elati, Wafaa Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study aims to shed light on the methods followed by Prophet Muhammad -peace be upon him- in teaching and guiding Muslim women, as well as in dealing with modern issues and concepts related to women. The study also attempts to understand the components of the prophetic discourse for women and how to apply them in contemporary life. This study is of great importance, as it sheds light on the spirituality and wisdom that the Prophet -peace be upon him- possessed in dealing with women, and how to guide and teach them. It also sheds light on how to deal with modern issues and contemporary concepts with wisdom and deep understanding of Islam and its teachings, and contribute to a better. In general, this study can contribute to enriching knowledge about the role of women in Islam and how to guide and educate them based on prophetic methods. It may also understand of women’s issues in Muslim societies and how to deal with them in a manner that is consistent with Islamic teaching.
Keywords: Prophetic speech; Women; Methods; Purposes